Influence of metallic nanoparticles on the performance of organic electrophosphorescence devices - Choulis, Stelios A.; Mathai, Mathew K.; Choong, Vi-En (My University, 2006)
We investigate the influence of metallic nanoparticles on the performance of phosphorescence organic light emitting diodes. The metallic nanoparticles display appropriate surface plasmon resonances in the visible region of the spectrum close to the emission band of the triplet emitter to accelerate the spontaneous emission rate of the phosphorescence compound. We have incorporated gold nanoparticles in the interface between alternative buffer layers and a phosphorescence based light emitting layer. In the case of AI4083 poly(3,4-ethylenedioxy thiophene):poly(styrene sulfonate) buffer layer, the interface modification with gold nanoparticles results in a 33% improvement in the luminance efficiency of tris(2-4(4-toltyl)phenylpyridine) iridium based phosphorescence organic light emitting diodes
Keywords: Light emitting diodes; Phosphorescence; Nanostructured materials; Luminescence